The role of exporting and trade for entry over the business cycle - George Alessandria; Horag Choi (Asian Development Bank Institute (ADBI), 2017)
This paper studies the role of international trade and the export participation decisions of establishments for firm creation over the business cycle in a general equilibrium model. The model captures two key features of establishment and exporter dynamics: i) new establishments start small and grow over time and ii) exporters tend to be bigger and more productive than non-exporters. When the cost of creating establishments fluctuates with aggregate productivity, we find the model can generate procyclical fluctuations in the stock of domestic establishments and importers similar to the data. Without international trades, entry is weakly countercyclical. The model also generates fluctuations in the stock of importers, exporters, and domestic establishments of similar magnitude to those in the data. With an entry margin, we also find that output is hump-shaped following a productivity shock since investments in creating establishments and exporters generate an incentive to delay accumulating physical capital.
Keywords: E31; F12; 330; Sunk cost; fixed cost; establishment heterogeneity; entry; exporter